The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.1039/d3ta00408b
|View full text |Cite
|
Sign up to set email alerts
|

CO2 reduction on the Li–Ga liquid metal surface

Abstract: Reducing CO2 emissions is crucial for the future survival of the planet and the demand for innovative technologies to capture and reduce CO2, focusing on global net-zero carbon emissions is...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 44 publications
0
7
0
Order By: Relevance
“…78 During the reaction, the dissolved Li metal migrated to the liquid−gas interface and instigated the dissociation of CO 2 into carbon and oxygen, while the Li content underwent an oxidation process. 79 Another investigation unveiled similar reaction mechanisms employing an innovative Mg−Ga liquid metal alloy to convert CO 2 into solid carbon. Initially, the Mg component diffused to the Mg−Ga alloy surface, facilitating the conversion of CO 2 to carbon, with the simultaneous oxidation of Mg to MgO.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 96%
See 2 more Smart Citations
“…78 During the reaction, the dissolved Li metal migrated to the liquid−gas interface and instigated the dissociation of CO 2 into carbon and oxygen, while the Li content underwent an oxidation process. 79 Another investigation unveiled similar reaction mechanisms employing an innovative Mg−Ga liquid metal alloy to convert CO 2 into solid carbon. Initially, the Mg component diffused to the Mg−Ga alloy surface, facilitating the conversion of CO 2 to carbon, with the simultaneous oxidation of Mg to MgO.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 96%
“…A recent study by Ye et al demonstrated a controllable Li–Ga liquid metal alloy system for the reduction of CO 2 into solid carbonaceous materials at low temperatures. During the reaction, the dissolved Li metal migrated to the liquid–gas interface and instigated the dissociation of CO 2 into carbon and oxygen, while the Li content underwent an oxidation process . Another investigation unveiled similar reaction mechanisms employing an innovative Mg–Ga liquid metal alloy to convert CO 2 into solid carbon.…”
Section: Liquid Metals In Catalysis Applicationsmentioning
confidence: 96%
See 1 more Smart Citation
“…Liquid metals are a genre of metals with low melting points, which are commonly referred to the family of post transition metals, e.g., gallium (Ga), indium (In), and bismuth (Bi). Unlike conventional solid metals, liquid metals, especially Ga, can remain in the liquid state at close to room temperature and can be utilized for alloying other metals into liquid-state mixtures. The electron-rich interface and liquid state of liquid metals endow great potential for facilitating chemical reactions and can be applied for the synthesis of miscellaneous functional materials. , …”
Section: Introductionmentioning
confidence: 99%
“…As a result, a number of dynamic processes such as dissolution, interdiffusion, and intermetallic formation can take place at the liquid–solid interface, leading to structural reconstruction and emergent phases. At or near room temperatures, liquid-metal gallium (Ga) and Ga-based alloys form intermetallic phases with many metals, particularly transition metals. , This liquid-metal-based intermetallic crystal growth method could be a promising route for designing bimetallic or multimetallic structures that are highly desirable for diverse applications such as catalysis and sensing. …”
mentioning
confidence: 99%